An ergatic control system with the stabilization counter of parameters of biological component - Поліщук, С. Т. (Problems of Informatization and Control, 2007)
An ergatic control system is analyzed. It is shown that, the increase of efficiency and reliability can be obtained in result adding of stabilization circuit for parameters of state vector of biological component